Gender differences in strength lateral asymmetries, limbs morphology and body composition in adolescent judo athletes - Mala, L.; Maly, T.; Camirelli, R.; Dornowski, M.; Zahalka, F.; Petr, M.; Hrasky, P.; Bujnovský, D (Archives of Budo, 2017)
Background and Study Aim: Maladaptive changes and asymmetries represent a high risk of adolescent injury in judo practice. Another health risk in judo is the manipulation of body weight to compete in the tactically most advantageous weight category. The aim of the study was the gender differences in body composition, upper limb muscle strength, upper and lower limb morphology in adolescent judo athletes.